PSYCHOLOGICAL POLLUTION AND ITS RELATIONSHIP TO THE ACCURACY OF SCORING IN FUTSAL AMONG FEMALE STUDENTS AT THE UNIVERSITY OF BABYLON - Hassan, Rouida Falih; Kaid, Mahmoud Adnan Mahmoud (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The research addressed psychological pollution, which is one of the important factors influencing scoring accuracy. The research problem included identifying the level of its impact on female students at the University of Babylon, as it is a game that many people love.Research objective:To determine the relationship between psychological pollution and scoring accuracy in soccer.Research hypothesis:There is a correlation between psychological pollution and scoring accuracy in soccer.The researchers used the descriptive approach using the survey method, as it is the appropriate method for formulating the problem. The research sample included (44) female students from the University of Babylon's futsal team for the academic year 2024-2025. It also included the research tools and tests used, the questionnaire, the pilot experiment, the main experiment, and statistical treatments.The researchers reached the following conclusions and recommendations:In light of the results and statistical treatments of the data obtained, the researchers reached the following conclusions:There are levels of both psychological pollution and scoring accuracy.The discrepancy between the stress level and the accuracy of their scoring is greater in women than in men.The researchers also reached the following recommendations:In light of the conclusions drawn from the research results, the researchers recommend the following:Emphasize psychological preparation during the implementation of the training curriculum.Pay attention to and study the psychological state of the player before and after playing matches.